Better than human : the promise and perils of enhancing ourselves - Buchanan, Allen E., 1948- (Philosophy in action., 2011)
Is it right to use biomedical technologies to make us better than well or even perhaps better than human? Should we view our biology as fixed or should we try to improve on it? College students are already taking cognitive enhancement drugs. The U.S. army is already working to develop drugs and technologies to produce "super soldiers." Scientists already know how to use genetic engineering techniques to enhance the strength and memories of mice and the application of such technologies to humans is on the horizon. In Better Than Human, philosopher-bioethicist Allen Buchanan grapples w.